Peary caribou (Rangifer tarandus pearyi) and muskoxen (Ovibos moschatus) on northwest Victoria Island, Northwest Territories - Davison, Tracy; Williams, Judy (Rangifer, 2013)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Normal tabell"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-fareast-language:EN-US; –> <!–[endif] –> An aerial population survey of Peary caribou (Rangifer tarandus pearyi) and muskoxen (Ovibus moschatus) on Victoria Island, Northwest Territories, was conducted in July 2010. The population estimate of adult Peary caribou was 150 ± 104 (95% Confidence Interval [CI]) was not significantly different than the 2005 estimate of 66 ± 61 (P < 0.05). There was also an estimate of 430 ± 214 (95% CI) adult Dolphin-Union caribou (R. t. groenlandicus x pearyi) in the study area. However, these caribou represent only a small portion of the Dolphin-Union herd. The population estimate of 11 442 ± 1637 (95% CI) adult muskoxen is not significantly different than the 2005 estimate of 12 062 ± 2156 (P < 0.05).